2013
DOI: 10.1037/a0031238
|View full text |Cite
|
Sign up to set email alerts
|

The development of face perception in infancy: Intersensory interference and unimodal visual facilitation.

Abstract: Although research has demonstrated impressive face perception skills of young infants, little attention has focused on conditions that enhance versus impair infant face perception. The present studies tested the prediction, generated from the Intersensory Redundancy Hypothesis (IRH), that face discrimination, which relies on detection of visual featural information, would be impaired in the context of intersensory redundancy provided by audiovisual speech, and enhanced in the absence of intersensory redundancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 70 publications
(188 reference statements)
4
46
0
Order By: Relevance
“…These 127 infants were part of a larger study in which mean performance for a variety of variables was reported, including total time to habituation, the look-away rate during habituation, the mean duration of the first two habituation trials, mean looking time over test trials, and visual recovery scores [2,31]. The durations of infants’ individual looks and the durations of total looking times within individual trials—the focus of the current study—have not been published.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These 127 infants were part of a larger study in which mean performance for a variety of variables was reported, including total time to habituation, the look-away rate during habituation, the mean duration of the first two habituation trials, mean looking time over test trials, and visual recovery scores [2,31]. The durations of infants’ individual looks and the durations of total looking times within individual trials—the focus of the current study—have not been published.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic color video displays of infant-directed speech served as the stimulus events [2,32–34]. Three actress’ faces and shoulders were videotaped as they recited “Mary Had a Little Lamb” (18 s) and “Jack and Jill” (12 s).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each eye contact the child made was coded when it occurred and in relation to which experimenter, adult pupil or teacher; (2) Contingent Reactivity, the degree of engagement, was evaluated as a repertoire of voluntary movements and facial expressions and then measured as high, intermediate and low (Csibra, 2010). Faces of people are highly salient to young infants and convey information for social interactions (Bahrick, Lickliter, & Castellanos, 2013);…”
Section: Codingmentioning
confidence: 99%